Reduced PGC-1β protein expression may underlie corticosterone inhibition of mitochondrial biogenesis and oxidative phosphorylation in chicken muscles - Li, Sheng; Wang, Zhi; Yao, Jing Wen; Jiao, Hong Chao; Wang, Xiao Juan; Lin, Hai; Zhao, Jing Peng (Frontiers in Physiology, 2022)
To uncover the molecular mechanism underlying glucocorticoid-induced loss of mitochondrial integrity in skeletal muscles, studies were performed to investigate whether the peroxisome proliferator-activated receptor γ coactivator 1 (PGC-1)-mediated pathway was involved in this process. In an in vivo trial, 3 groups of 30-d-old Arbor Acres male broilers were randomly subjected to one of the following treatments for 7 days: corticosterone (CORT, 30 mg/kg diet), control (blank), and pair-feeding (restricted to the same feed intake as for the CORT treatment), each with 6 replicates of 15 birds. Mitochondrial abundance, morphology, and function were determined in the pectoralis major and biceps femoris muscles. In an in vitro trial, a primary culture of embryonic chick myotubes was incubated with a serum-free medium for 24 h in the presence or absence of CORT (0, 200, and 1000 nM). Results showed that CORT destroyed mitochondrial ultrastructure (P < 0.01), and decreased the enzymatic activity and protein expression of respiratory chain complexes (P < 0.05), leading to an inferior coupling efficiency (P < 0.05). As reflected by a decline in mitochondrial density (P < 0.01) and mitochondrial DNA copy number (P < 0.05), CORT reduced mitochondrial contents. Among all three PGC-1 family members, only PGC-1β was down-regulated by CORT at the protein level (P < 0.05). Some aspects of these responses were tissue-specific and seemed to result from the depressed feed intake. Overall, CORT may impair mitochondrial biogenesis and oxidative phosphorylation in a PGC-1β-dependent manner in chicken muscles.